Optimization of The Electrical Complex Functioning Parameters of Water-Lifting Areas In Arctic Climate Conditions - Palkin G. A. (Российская Арктика, 2021)
The paper deals with the optimization of the electrical complex parameters of water-lifting areas in the difficult climatic conditions of the Arctic and similar regions. The aim of optimization is to minimize capital and operating costs at the stages of construction and functional of centralized water supply systems while ensuring a sufficient level of accident-free operation. The electrical complex of the water-lifting areas of the water supply system is the main source of economic costs, and also the most vulnerable to emergencies, the most dangerous of which is pipeline freezing. The key parameters affecting the technical and economic efficiency of this facility were identified, and the existing methods of changing them were classified. A mathematical and computer optimization model was developed to find the best values ​​for the selected parameters. The model was used to calculate the parameters of the electrical complex of the water-lifting section of the urban settlement Novoorlovsk of the Zabaykalskiy kray.